THE REACTION KINETICS OF ALANINE AND GLYCINE UNDER HYDROTHERMAL CONDITIONS - Cox J.S.; Seward T.M. (My University, 2007)
Experimental data on the hydrothermal reaction kinetics of α-alanine, glycine, and β-alanine were acquired using a custom-built spectrophotometric reaction cell which permits in situ observation under hydrothermal conditions. Quantitative kinetic information, including rate constants, concentration versus time profiles, and calculations of the individual component spectra, was obtained from the data using a self-modeling chemometric approach based on factor analysis which treats the rate expressions simultaneously as a system of differential algebraic equations (DAE) of index 1. Experimental data collected at 120-165 °C and 20 bar indicates that aqueous α-alanine, glycine and β-alanine will preferentially undergo dimerization and subsequent cyclization when heated in an inert reactor. The results presented here lend further support to the roles of temperature, exposed reactive surfaces, and matrix additives in the reaction kinetics of the structurally simple amino acids examined in this study. © 2007 Elsevier Ltd. All rights reserved.